Appendicitis in a deployed military setting: diagnosis, management and impact on the fighting force. Issue 2 (7th April 2016) - Howes, Rachel; Webster, C; Garner, J
Abstract : Background: Acute appendicitis is a principal cause of abdominal pain worldwide and most common in young men who constitute the majority of the deployed fighting force. Diagnostic accuracy is paramount to prevent unnecessary intervention, morbidity and force impact. Method: A consecutive series of appendicectomies, performed over 28 months on deployment in Afghanistan, was evaluated to assess the negative appendicectomy (NA) rate, explore the impact of CT on the rates of NA and assess the impact of appendicectomy on manpower in the deployed workforce. Results: In Afghanistan, the operative NA rate was 9.6%, whereas the histological NA rate was 20.5%. CT was widely used in Afghanistan (36%) and there was a significant reduction in NA rates if CT was performed preoperatively (6.25% vs 26%, p=0.02). Conclusions: Diagnostic imaging will be limited in future conflicts and reliance on clinical judgement will be necessary. Military clinicians may need to accept higher rates of NA, as prolonged observation may not be possible. CT scanning should be used to a greater extent when available. A conservative management strategy for appendicitis with appropriate antibiotics should be considered in the event of delayed transfer to a surgical facility.